2017
DOI: 10.1007/s12032-017-0893-6
|View full text |Cite
|
Sign up to set email alerts
|

Does p53 codon 72 polymorphism have a prognostic value in carcinoma of the vulva and vagina?

Abstract: Human papilloma virus (HPV) is considered to be responsible for a large part of vaginal and vulvar carcinomas, and the p53 codon 72 polymorphism has been implicated in susceptibility to cancer induced by this virus, but with contradicting results. In this study, we have investigated the prognostic value of the codon 72 polymorphism by real-time PCR (qPCR) in two cohorts of vaginal (n = 66) and vulvar (n = 123) carcinomas. In vaginal carcinoma, arginine homozygous patients were significantly associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Over-expression of both DNMT3A and DNMT3B was associated with an increased risk of vulvar local recurrence (univariate HR 4.51 (95% CI 1.40, 14.49), HR 5.69 (95% CI 1.17, 27.57) respectively) [32]. Furthermore, Qvick et al reported on the prognostic value of p53 codon 72 polymorphism [33]. A similar local recurrence rate in tumors with arg/arg genotype and in tumors with arg/pro or pro/pro genotype was observed.…”
Section: Remaining Factorsmentioning
confidence: 99%
“…Over-expression of both DNMT3A and DNMT3B was associated with an increased risk of vulvar local recurrence (univariate HR 4.51 (95% CI 1.40, 14.49), HR 5.69 (95% CI 1.17, 27.57) respectively) [32]. Furthermore, Qvick et al reported on the prognostic value of p53 codon 72 polymorphism [33]. A similar local recurrence rate in tumors with arg/arg genotype and in tumors with arg/pro or pro/pro genotype was observed.…”
Section: Remaining Factorsmentioning
confidence: 99%
“…Recently, a large number of studies have investigated the association between TP53 codon 72 polymorphisms and BC, including mechanism research, cancer susceptibility and prognosis 22 , 44 , 51 . As reported by Kung, increased growth arrest and decreased apoptosis were found in R72 cells compared with P72 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in several HPV-related cancers (e.g. oral cancer, cervical cancer, vulvar and vaginal carcinoma) disease risk was shown to be influenced by the p53 p.Arg72Pro SNP 17 - 19 suggesting the p.72Arg variant as a risk factor for cancer development in high risk HPV positive individuals. But also in non HPV-related tumor types p53 codon 72 SNP was shown to influence disease risk 20 - 22 .…”
Section: Introductionmentioning
confidence: 99%